Role and common types of herbal medicine used for oral health in the Middle-East - Khbrani, Abdulrahman Hussain; Al-Shahrani, Adel Abdulrahman; Alzahrani, Huda Gurmallah; Almalki, Ahmad Daifallah; Alhawsaw, Faizah Faez; Almalki, Waleed Daifallah; Almutairi, Khalaf Muthyib; Zahrani, Asmaa Gurmallah Al (International Journal Of Community Medicine And Public Health, 2022)
Herbal therapies are used worldwide to treat health conditions. In Middle Eastern countries, since ancient generations, herbal medicine has been used for oral health because of cultural and religious norms. Antiseptic, antibacterial, antimicrobial, antifungal, antioxidant, antiviral agents, and analgesic derived from plants are of widespread interest in dentistry. The properties of herbal medicine are used to treat toothache, gum inflammation, canker sores, halitosis, gingivitis, and periodontitis, as well as tooth decay. The popular herbs and spices used in treating dental disorders in Middle Eastern countries are cloves, miswak, thyme, green tea, peppermint, rosemary, olive oil, myrrh, anise, sesame, ginger, and garlic. Based on the available evidence from research demonstrating the antibacterial, antimicrobial, analgesic, and antiplaque effects of these herbs used in Middle Eastern countries, they could still be useful as an alternative treatment for gingivitis, periodontal diseases, or antiplaque agents. However, more clinical data is required to ascertain the benefits of herbal medicine for oral tissues and the prevention of oral diseases.